Comparing older and younger adults' traversal time in expandable and non-expandable hierarchical structures - Kurniawan, Sri Hastuti; Ellis, R. Darin; Zaphiris, Panayiotis (My University, 2002)
The present study investigates time and click error differences when older and younger computer users traversed expandable and non-expandable online hierarchical information structures to reach a target. The results show that older users were slower but did not make more errors than their younger counterparts, suggesting more cautious decision making. The study did not show superiority of either hierarchy in terms of traversal time but the expandable hierarchy resulted in fewer errors to get to the target. Although older users significantly rated their computer and Internet experience lower than younger participants, experience did not alter the significance of age and hierarchy differences.